Description of Adolescent Understanding at SMK Negeri 9 Padang on the Dangers of Drug Abuse - Annisa Pertiwi; Yeni Karneli; Afdal Afdal (Universitas Negeri Padang, 2019)
Drug abuse in adolescents is increasingly margined, drug abuse can cause a variety of negative impacts. Understanding is one of the most important aspects in the prevention of drug abuse. This research aims to determine the understanding of adolescents in SMK Negeri 9 Padang on the Dangers of Drug Abuse. This research uses quantitative descriptive methods. The population of this research was 435 students of class X of SMK Negeri 9 Padang. The research sample was 204 students. Based on research results 145 students (71%) Have an understanding of the dangers of drugs in the sufficient category, 55 students (27%) In good category, and 4 students (2%) In the less category. Understanding of students in SMK Negeri 9 Padang, the majority of which are in sufficient category and some students are in the category of less must be sought to be more improved.